De novo TRIM8 variants impair its protein localization to nuclear bodies and cause developmental delay, epilepsy, and focal segmental glomerulosclerosis. - Weng, Patricia L; Majmundar, Amar J; Khan, Kamal; Lim, Tze Y; Shril, Shirlee; Jin, Gina; Musgrove, John; Wang, Minxian; Ahram, Dina F; Aggarwal, Vimla S; Bier, Louise E; Heinzen, Erin L; et al. (Am J Hum Genet, 2021)
Focal segmental glomerulosclerosis (FSGS) is the main pathology underlying steroid-resistant nephrotic syndrome (SRNS) and a leading cause of chronic kidney disease. Monogenic forms of pediatric SRNS are predominantly caused by recessive mutations, while the contribution of de novo variants (DNVs) to this trait is poorly understood. Using exome sequencing (ES) in a proband with FSGS/SRNS, developmental delay, and epilepsy, we discovered a nonsense DNV in TRIM8, which encodes the E3 ubiquitin ligase tripartite motif containing 8. To establish whether TRIM8 variants represent a cause of FSGS, we aggregated exome/genome-sequencing data for 2,501 pediatric FSGS/SRNS-affected individuals and 48,556 control subjects, detecting eight heterozygous TRIM8 truncating variants in affected subjects but none in control subjects (p = 3.28 × 10). In all six cases with available parental DNA, we demonstrated de novo inheritance (p = 2.21 × 10). Reverse phenotyping revealed neurodevelopmental disease in all eight families. We next analyzed ES from 9,067 individuals with epilepsy, yielding three additional families with truncating TRIM8 variants. Clinical review revealed FSGS in all. All TRIM8 variants cause protein truncation clustering within the last exon between residues 390 and 487 of the 551 amino acid protein, indicating a correlation between this syndrome and loss of the TRIM8 C-terminal region. Wild-type TRIM8 overexpressed in immortalized human podocytes and neuronal cells localized to nuclear bodies, while constructs harboring patient-specific variants mislocalized diffusely to the nucleoplasm. Co-localization studies demonstrated that Gemini and Cajal bodies frequently abut a TRIM8 nuclear body. Truncating TRIM8 DNVs cause a neuro-renal syndrome via aberrant TRIM8 localization, implicating nuclear bodies in FSGS and developmental brain disease.
Keywords: Adult; Animals; Carrier Proteins; Cell Line; Child; Child, Preschool; Codon, Nonsense; Developmental Disabilities; Epilepsy; Female; Glomerulosclerosis, Focal Segmental; Humans; Intranuclear Space; Kidney; Male; Mice; Mutation; Nephrotic Syndrome; Nerve Tissue Proteins; Phenotype; Podocytes; Whole Exome Sequencing

DAAM2 Variants Cause Nephrotic Syndrome via Actin Dysregulation. - Schneider, Ronen; Deutsch, Konstantin; Hoeprich, Gregory J; Marquez, Jonathan; Hermle, Tobias; Braun, Daniela A; Seltzsam, Steve; Kitzler, Thomas M; Mao, Youying; Buerger, Florian; Majmundar, Amar J; Onuchic-Whitford, Ana C; et al. (Am J Hum Genet, 2020)
The discovery of >60 monogenic causes of nephrotic syndrome (NS) has revealed a central role for the actin regulators RhoA/Rac1/Cdc42 and their effectors, including the formin INF2. By whole-exome sequencing (WES), we here discovered bi-allelic variants in the formin DAAM2 in four unrelated families with steroid-resistant NS. We show that DAAM2 localizes to the cytoplasm in podocytes and in kidney sections. Further, the variants impair DAAM2-dependent actin remodeling processes: wild-type DAAM2 cDNA, but not cDNA representing missense variants found in individuals with NS, rescued reduced podocyte migration rate (PMR) and restored reduced filopodia formation in shRNA-induced DAAM2-knockdown podocytes. Filopodia restoration was also induced by the formin-activating molecule IMM-01. DAAM2 also co-localizes and co-immunoprecipitates with INF2, which is intriguing since variants in both formins cause NS. Using in vitro bulk and TIRF microscopy assays, we find that DAAM2 variants alter actin assembly activities of the formin. In a Xenopus daam2-CRISPR knockout model, we demonstrate actin dysregulation in vivo and glomerular maldevelopment that is rescued by WT-DAAM2 mRNA. We conclude that DAAM2 variants are a likely cause of monogenic human SRNS due to actin dysregulation in podocytes. Further, we provide evidence that DAAM2-associated SRNS may be amenable to treatment using actin regulating compounds.
Keywords: Actins; Alleles; Animals; Animals, Genetically Modified; Cell Movement; Cytoplasm; Formins; Genetic Variation; Humans; Kidney; Kidney Glomerulus; Microfilament Proteins; Mutation, Missense; Nephrotic Syndrome; Podocytes; Pseudopodia; rho GTP-Binding Proteins; RNA, Small Interfering; Whole Exome Sequencing; Xenopus